THE EFFECTS OF MIXED MARRIAGE LAWS ON THE DIVISION OF PROPERTY UNDER THE MARRIAGE LAW AND INTERNATIONAL CIVIL PRINCIPLES - Sidabutar, Octaviana; Amalia, Lia; Abas, Muhamad (Awang Long Law Review, 2024)
Blended marriage alludes to a marriage connection between people of various identities. This outcomes in legitimate ramifications in regards to the division of joint resources. This exploration expects to investigate comprehension of blended relationships as per Regulation Number 1 of 1974 concerning Marriage and according to the viewpoint of global confidential regulation, as well as the lawful results of partitioning joint resources in blended relationships. By utilizing optional legitimate sources, this exploration utilizes a Standardizing Juridical examination technique, in particular by checking out at speculations, legal guidelines and case regulation. As per Marriage Regulation Number 1 of 1974, blended relationships happen on the off chance that one accomplice is an Indonesian resident and the other isn't. This happens when two individuals whose regulations are not quite the same as Indonesian regulation wed in Indonesia. With regards to the authorization of the Marriage Regulation, there are two sorts of conjugal resources, in particular acquired resources (individual resources) and joint resources. All in all, blended relationships are managed in Regulation Number 1974 concerning Marriage and in Global Confidential Regulation applying the standard of lex loci festivities, which expresses that the law that applies to the marriage is the law where the marriage happens, and the division of joint property is directed as per law of each party.